2008
DOI: 10.2135/cropsci2007.05.0295
|View full text |Cite
|
Sign up to set email alerts
|

Hybridization and Introgression between Two Diploid Wild Relatives of White Clover, Trifolium nigrescens Viv. and T. occidentale Coombe

Abstract: Trifolium nigrescens Viv. and T. occidentale Coombe are diploid (2n = 2x = 16) clover species with contrasting habits and geographic distributions. Trifolium nigrescens is a nonstoloniferous annual with widespread distribution in the Mediterranean countries of Europe and northern Africa, Turkey, the Middle East, and the Caucasus region. By contrast, T. occidentale is a stoloniferous perennial and is strictly coastal, occurring on the Gulf Stream coasts of Portugal, Spain, France, Ireland, and the United Kingdo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…The identity of the ancestors has remained elusive and, despite many attempts [e.g. [3,5-7] there has been no successful re-synthesis. A phylogenetic analysis of Trifolium based on the nuclear internal transcribed spacer region of 18 S–26S rDNA (ITS) and chloroplast trnL intron DNA (cpDNA) sequences [8] suggested that the closest extant diploid ancestors were T. pallescens (2n=2x=16) and T. occidentale (2n=2x=16) .…”
Section: Introductionmentioning
confidence: 99%
“…The identity of the ancestors has remained elusive and, despite many attempts [e.g. [3,5-7] there has been no successful re-synthesis. A phylogenetic analysis of Trifolium based on the nuclear internal transcribed spacer region of 18 S–26S rDNA (ITS) and chloroplast trnL intron DNA (cpDNA) sequences [8] suggested that the closest extant diploid ancestors were T. pallescens (2n=2x=16) and T. occidentale (2n=2x=16) .…”
Section: Introductionmentioning
confidence: 99%
“…Supporting this hypothesis is also the fact that, unlike T. repens and T. nigrescens, all the T. occidentale and T. pallescens accessions tested to date are acyanogenic [67,68]. Furthermore, cross-hybridisation of diploid T. nigrescens with artificially doubled [63,69,70] and diploid T. occidentale [71] can be achieved without the aid of special techniques, while hybridisation of T. pallescens and T. occidentale could only be achieved by embryo rescue (Williams, personal communication).…”
Section: T Repens and Its Putative Progenitorsmentioning
confidence: 99%
“…It is likely that T. nigrescens and T. occidentale are close relatives on one side of the ancestry of white clover. In the light of the recent evidence as reported by Ansari et al (2004), Ellison et al (2006) and Williams et al (2008) it seems that the ancestry of the allopolyploid white clover remains elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic Southern hybridization and/or fluorescence in situ hybridization (FISH) performed on 17 Trifolium species/subspecies by Ansari et al (2004) revealed that it is a conserved lineage-specific repeat confined to several species within the section Lotoidea originating in the Mediterranean region. Williams et al (2008) reported evidence suggesting that T. nigrescens is a close relative of T. occidentale but not a direct ancestor of white clover. It is likely that T. nigrescens and T. occidentale are close relatives on one side of the ancestry of white clover.…”
Section: Introductionmentioning
confidence: 99%